FATAL INTOXICATION AFTER DELIBERATE INGESTION OF 2-METHYL-4-CHLOROPHENOXYACETIC ACID (MCPA) - Petkovska, Lidija; Pereska, Zanina; Simonovska, Natasha; Babulovska, Aleksandra; Kostadinoski, Kristin; Jakjimovska, Angelina; Milosheska, Eleonora; Kacarska Geshoski, Marijana (Journal of Morphological Sciences; Vol 7 No 1 (2024): JMS, 2024)
Although intentional poisonings with 2-Methyl-4-chlorophenoxyacetic acid (MCPA) are relatively rare and in most cases cause moderate toxicity, deaths have been described, mainly due to cardiorespiratory arrest. Treatment is generally supportive, with opposing effects from the application of urinary alkalization and other methods for secondary elimination of the poison.  Case report:  Herein we report a case of an adult female who was admitted to theUniversity Clinic for Toxicology several hours after a suicidal ingestion of an unknown toxic agent that resulted in vomiting and loss of consciousness. After MCPA ingestion was confirmed, she received supportive care, urinary alkalinization, and hemodialysis. Despite this, the patient was hypotensive, after which signs of acute kidney injury, rhabdomyolysis, hyperamylasemia, hepatic lesion, electrolyte abnormalities, metabolic acidosis, disseminated intravascular coagulation, and respiratory failure developed. Despite applied mechanical ventilation and inotropic support, the patient died several days later. MCPA is a poisonous herbicide that can cause severe forms of poisoning and fatal outcome especially after large intentional ingestions. The availability of rapid qualitative toxicological confirmation of the xenobiotic can contribute to early etiological diagnosis and initiation of appropriate therapeutic measures that would improve survival even in more severe forms. Keywords: 2-Methyl-4-chlorophenoxyacetic acid, herbicide, poisoning, treatment.